Process Drama in Civic Education: Balancing Student Input and Learning Outcomes in a Playful Format - Eva Hallgren; Eva Österlind (Education Sciences, 2019)
The purpose is to investigate process drama for teaching civics, mainly democracy and migration. Process drama implies students and teacher to take on roles, to explore a subject content collectively. The study is based on a secondary school educational initiative where a drama pedagogue was invited to address civics through process drama. Four civic lessons were video recorded and analyzed through an activity theory framework. From this perspective, process drama can be understood as two activities with different motives/objects, the educational and the fictional, where the fictional activity should have a playful format. The results show that the dialogical approach used by the drama pedagogue created a democratic opportunity and also established the playful format. The students’ engagement was notably high. However, it was obvious there were no challenging or probing questions being asked by the drama pedagogue or the civics teacher, neither in nor out of role. As a consequence, the full learning potential of process drama in civics education could not be achieved. We suggest a co-teaching approach between civic teachers and drama pedagogues, to overcome challenges in using process drama in civic education for learning objectives to be attained.